The Effect of Earnings Management Based on Discretionary Accruals on the Cost of Equity Capital of Listed Companies with the Control of Firm Size, Financial Leverage, and Growth Opportunities - Pourkhurshid , Hasan; Armon Manesh, Zeinab (Business, Marketing, and Finance Open, 2025)
The purpose of this study was to investigate the effect of earnings management based on discretionary accruals on the cost of equity capital in listed companies, while controlling for the effects of firm size, financial leverage, and growth opportunities as control variables. The statistical population consisted of companies listed on the stock exchange, and after applying conventional screening criteria (excluding financial firms, firms with changes in fiscal year-end, and firms with insufficient data), a sample of 128 companies (896 firm-year observations) was selected for the period 2017–2023. Earnings management through discretionary accruals was measured using the Modified Jones Model, while the cost of equity capital was estimated using the Gordon Growth Model/dividend growth approach (and earnings-based models in the robustness test). Panel regression analysis was employed to test the research hypotheses. The results indicated that the coefficient of discretionary accruals was positive and statistically significant (t = 3.12, β = 0.041, p < .01). This finding suggests that an increase in accrual-based earnings management leads to a higher cost of equity capital. Furthermore, firm size had a negative and significant effect on the cost of capital (β = -0.018, p < .05), whereas financial leverage demonstrated a positive and significant effect (β = 0.067, p < .01). Growth opportunities also exhibited a positive effect (β = 0.012, p < .10). The explanatory power of the model was assessed as acceptable (Adjusted R² = 0.29). The findings confirm that accrual-based earnings management can increase informational risk and investor uncertainty, thereby increasing shareholders’ required rate of return (cost of capital).